Conjoined thoracopagus twins - (:unkn) unknown (My University, 2000)
A pair of conjoined thoracopagus twins was delivered vaginally after appropriate antepartum diagnosis. Obstetrical management of conjoined twins is more likely to be successful when antepartum diagnosis of fetal anomalies, gestational age and fetal viability are evaluated. This can be done when conjoining is suspected with any twin gestation. Ultrasonography is confirmatory but not diagnostic. Conjoining must be suspected in a gravid mother with multifetal gestations and abnormal fetal attitude. When the images cannot be separated ultrasonographically, antepartum roentgenographic examination and/or amniographic examination should be performed. As conjoined twinning has very high morbidity and mortality, the appropriate route of delivery should be chosen, usually elective cesarean section. Conjoined twinning is one of the rare congenital malformations resulting from incomplete, delayed fusion of the embryonic disc, which occurs after the 14th day of fertilization. In this report we present a case of conjoined thoracopagus twins and discuss the obstetric management of this condition in the light of previous literature. (C) 2000 Science Reviews.
Keywords: Conjoined twins; Thoracopagus